2009
DOI: 10.1074/jbc.m807641200
|View full text |Cite
|
Sign up to set email alerts
|

MAFbx/Atrogin-1 Controls the Activity of the Initiation Factor eIF3-f in Skeletal Muscle Atrophy by Targeting Multiple C-terminal Lysines

Abstract: We recently presented evidence that the subunit eIF3-f of the eukaryotic initiation translation factor eIF3 that interacts with the E3-ligase Atrogin-1/muscle atrophy F-box (MAFbx) for polyubiquitination and proteasome-mediated degradation is a key target that accounts for MAFbx function during muscle atrophy. To understand this process, deletion analysis was used to identify the region of eIF3-f that is required for its proteolysis. Here, we report that the highly conserved C-terminal domain of eIF3-f is impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 27 publications
5
53
0
Order By: Relevance
“…Interestingly, we observed concomitant changes in atrogin-1 expression and in phosphorylation levels of mTOR targets involved in mRNA translation into proteins (e.g., lower phosphorylation of S6K1, S6 and 4EBP1 in P− vs. P+). These findings may corroborate recent evidence indicating that atrogin-1 is related to muscle protein synthesis and growth through the regulation of downstream effectors of mTOR, and that the activity or inactivity of a common set of molecules controlling specific cellular pathways determines whether the skeletal muscle tissue will respond to defined stimuli with muscle growth or loss [13,43,44]. eIF3f has been characterized as a substrate of atrogin-1 [45].…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, we observed concomitant changes in atrogin-1 expression and in phosphorylation levels of mTOR targets involved in mRNA translation into proteins (e.g., lower phosphorylation of S6K1, S6 and 4EBP1 in P− vs. P+). These findings may corroborate recent evidence indicating that atrogin-1 is related to muscle protein synthesis and growth through the regulation of downstream effectors of mTOR, and that the activity or inactivity of a common set of molecules controlling specific cellular pathways determines whether the skeletal muscle tissue will respond to defined stimuli with muscle growth or loss [13,43,44]. eIF3f has been characterized as a substrate of atrogin-1 [45].…”
Section: Discussionsupporting
confidence: 80%
“…Support for this contention comes from data showing that elevations in the early stage of disuse could be targeting the degradation of translational proteins such as eukaryotic initiation factor 3F. 99,100 The reduction in the content of these proteins subsequently serves to limit the capacity of the translational machinery to mount a sufficient response to anabolic stimulation necessary to sustain positive protein balance. Although to our knowledge, no study has identified if a period of muscle disuse in humans results in the targeted degradation of these proteins and, as such, this hypothesis awaits experimental confirmation.…”
Section: The Impact Of Aging and Unloadingmentioning
confidence: 92%
“…75 This E3 is upregulated and essential for accelerated muscle protein loss in a number of disorders. 76 Ubiquitylation of eIF3f occurs on multiple (6) lysines in the Cterminus 74 and results in its ubiquitin-mediated proteolysis in myotubes undergoing atrophy. Under these conditions both MAFbnx and eIF3f are detected in the nucleus.…”
Section: Eif3mentioning
confidence: 99%
“…Its role as a translational enhancer came to light in a study on muscle atrophy. 74 Here, eIF3f is ubiquitylated by the MAFbnx/ Atrogin1 protein which is a muscle-specific F-box protein ubiquitin E3 ligase. 75 This E3 is upregulated and essential for accelerated muscle protein loss in a number of disorders.…”
Section: Eif3mentioning
confidence: 99%